Communicating the "world-class" city: a visual-material approach. Issue 1 (1st January 2021) - Aiello, Giorgia
ABSTRACT: In this article, I demonstrate my visual-material approach to researching the urban built environment as a medium of communication in its own right. Specifically, I discuss my research on second-tier cities with "world-class" aspirations, which highlights the significance of both symbolic and material resources in processes of urban regeneration and redevelopment. A visual-material approach draws not only from social semiotics and multimodality, but also from critical and material rhetoric to engage with the ways in which increasingly widespread "formats" of urban regeneration and redevelopment are mobilized to transform the urban built environment in the service of a globally appealing aesthetic. In doing so, this is also an approach that illuminates the dialectical relationship between cities' perceived necessity to appear competitive on a heavily mediatized global stage and to intervene on their landscape in ways that mediate the everyday lives of urban communities in lasting ways.